Pengembangan Media Padat untuk Menumbuhkan Mycobacterium bovis (DEVELOPMENT OF SOLID MEDIUM FOR MYCOBACTERIUM BOVIS CULTIVATION) - Daulay, Mazdani Ulfah; Sudarwanto, Mirnawati; Nugroho, Widagdo Sri; Sudarnika, Etih (Jurnal Veteriner, 2016)
Mycobacterial culture provides definitive diagnosis of tuberculosis (TB), but commercially readyto-use culture media for Mycobacterium bovis are rarely available. The aims of this study were todevelop and to evaluate the ability of M. Bovis to grow in Modified Ogawa Agar (MOA) in comparisonwith the available culture media, such as Löwenstein Jensen (LJ) and Modified Ogawa (MO). Eachmedia were inculation with 0.1 ml suspension of 105 CFU/mL M. bovis and M. phlei in PhosphateBuffer Saline (PBS) and each media was replicated in five tubes. Mycobacterium phlei grew in everymedium since day 4. M. bovis grew in media LJ and MO since day 17, but failed to grow in mediumMOA. The recovery rate of M. phlei in LJ and MOA were significantly different. The ability of MOA tocultivate M. phlei was different from LJ. Colonies of M. phlei in MOA were easier to be harvested, muchsimpler to prepare, and more feasible than medium LJ. The recovery rate of M. bovis in media LJ andMO were not significantly different, but medium MO were much simpler to prepare and more feasiblethan medium LJ. Media MOA were able to cultivate M. phlei, but proven unable to cultivate M. bovisin this research.
Keywords: Mycobacterium bovis; mycobacterial culture; culture media